William Varner, The Apostolic Fathers. An Introduction and Translation, T&T Clark, London 2023, pp. 242 - Misiarczyk, Leszek (Vox Patrum, 2023)
Review of the book: W. Varner, The Apostolic Fathers. An Introduction and Translation, T&T Clark, London 2023.